Digital Health - Linwood, Simon Lin (Exon Publications, 2022)
Digital health has undergone an astounding transformation since the beginning of the COVID-19 pandemic. Almost all fields of medicine have adopted digital technologies to deliver patient care. Rapid advances in artificial intelligence, Big Data, augmented reality, Internet of Medical Things, connected devices, robotics, and algorithms will revolutionize digital health in almost all fields of medicine in the future. With the widespread use of smartphones, downloadable or internet-based applications (apps) will play a major role in the diagnosis of diseases, and monitoring and management of patients. However, the implementation of digital health is not without challenges and concerns. These include security and privacy of patient data, lack of a universal legal and regulatory framework, accountability, data ownership, and health inequity, among others. Despite these challenges and concerns, it is undeniable that digital health has revolutionized patient care and will continue to do so. The chapters of this open access book are examples of such revolution, challenges, and concerns. A multidisciplinary team of clinicians and researchers provide a balanced discussion of the benefits and challenges of digital health in ophthalmology, oncology, chronic obstructive respiratory diseases, transfusion medicine, stroke, opioid crisis, and the care of elderly. Also, there are chapters addressing the concerns of health inequity, and the risks and security of patient-generated data. This is a timely open access book not only for clinicians, but also for everyone who is interested in transformation of health care to digital health care.